Communication of orang asli muallaf with their Malay counterparts - Razaleigh Muhamat @ Kawangit; Abdul Ghafar Don; Anuar Puteh (Universiti Kebangsaan Malaysia, 2013)
This research set outs to explore the exact level of interaction between Orang Asli Muallaf and their Malay counterparts in Malaysia. It was sure that interaction in social aspect becomes dilemma when the Muallaf convert from their own religion to Islām. It suggests that when these converts begin to practise Islām, their behaviour changes in line with the identity of the Malays. This is because Islām equates to Malay in the Malaysian context. Whilst they are welcomed by their Malay counterparts, it is nevertheless hypothesised that they may not interact fully into the Malay culture.